The Visegrád Four. Ghosts or demons? (Economic and Political Thought, 2018)
Based on the monograph by Ivo van de Wijdeven, Visegrád’s ghosts: Unknownhistory of Poland, Hungary, the Czech Republic and Slovakia [j. nid.De spoken van Visegrád, De onbekende geschiedenis van Polen, Hongarije,Tsjechië en Slowakije], published in the Netherlands in April 2018 and thematerials from the international conference “Place and role of the VisegrádGroup states in the European Union” at Lazarski University, the authorattempts to look at the issues from the point of view of a foreign readerand the Visegrád Group states’ diplomats, the conference participants. Thediplomats demonstrated official optimism and determination, and they urgedthat a forum like the Visegrád Group is necessary, and they decidedly refuteda hypothesis that it is a competitive structure with the European Union. Thescientists, more critical in nature, drew attention to the differences betweenthe V4 states in order to illustrate the threats resulting from interest clashes,e.g. particular states’ attitudes to Russia. Everybody agreed that the V4 statesface a great test, i.e. joint protection of the shape of the coherence policy andthe best possible distribution of resources in the future budget.The author of the first monograph devoted to the V4 states written inDutch, in its conclusions, presents the opinion that the future of Europe,both the European Union and the Visegrád Four, depends on the answer tothe question whether the Member States are able to translate their differentinterests into their common strength instead of common weakness.
Keywords: Visegrád Group, European Union, the Netherlands, Poland, conference